2019
DOI: 10.1002/ptr.6552
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the clinical use of Withania somnifera (Ashwagandha) to ameliorate cognitive dysfunction

Abstract: Many developed countries are experiencing a rapidly “greying” population, and cognitive decline is common in the elderly. There is no cure for dementia, and pharmacotherapy options to treat cognitive dysfunction provide limited symptomatic improvements. Withania somnifera (Ashwagandha), a popular herb highly valued in Ayurvedic medicine, has often been used to aid memory and cognition. This systematic review thus aimed to evaluate the clinical evidence base and investigate the potential role of W. somnifera in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Several systematic reviews and assessment reports have been conducted on the clinical efficacy and safety of ginseng, 2,372–374 Eleutherococcus , 375 Rhodiola , 376–382 Withania , 383–388 and other adaptogens on several indications such as cognitive function, 33,72 cardiovascular diseases, 389 chronic pulmonary disease, 390 prevention of common cold, 391 and erectile dysfunction 392 . The clinical evidence of the benefits of W. somnifera in male infertility is also promising but very limited to provide sufficiently robust evidence because of the small number of eligible studies and available data 393 .…”
Section: Current and Prospective Use Of Adaptogens In Stress‐induced mentioning
confidence: 99%
See 1 more Smart Citation
“…Several systematic reviews and assessment reports have been conducted on the clinical efficacy and safety of ginseng, 2,372–374 Eleutherococcus , 375 Rhodiola , 376–382 Withania , 383–388 and other adaptogens on several indications such as cognitive function, 33,72 cardiovascular diseases, 389 chronic pulmonary disease, 390 prevention of common cold, 391 and erectile dysfunction 392 . The clinical evidence of the benefits of W. somnifera in male infertility is also promising but very limited to provide sufficiently robust evidence because of the small number of eligible studies and available data 393 .…”
Section: Current and Prospective Use Of Adaptogens In Stress‐induced mentioning
confidence: 99%
“…In five studies conducted in patients with anxiety and stress, significant (in most cases) improvements were observed with Withania intervention as compared with placebo, but cases of potential bias were identified 383 . There is some evidence from randomized, placebo‐controlled, double‐blind trials regarding the benefits of W. somnifera on cognitive function, such as improved performance on cognitive tasks, attention, and reaction time 385 . However, the study population was heterogeneous, including older adults with mild cognitive impairment and adults with schizophrenia, schizoaffective disorder, or bipolar disorder.…”
Section: Current and Prospective Use Of Adaptogens In Stress‐induced mentioning
confidence: 99%
“…Withania somnifera has many biological properties such as antioxidant, anti-inflammatory, neuroprotective, anti-depression, anti-stress, and immunomodulatory [ 164 ]. In a double-blind, randomized, and placebo-controlled trial is has been proven that the administration of ashwaganda-root extract (600 mg/day for eight weeks) increases memory, executive function, and information processing speed and also enhances cognitive functions in adult patients suffering from a mild mental weakening [ 165 , 166 ]. The extract with withaferin A and sitoindoside VII-X (50 mg/kg p.o.…”
Section: Antioxidants As the Prevention And Treatment Of Depression And Admentioning
confidence: 99%
“…Although it has been used therapeutically for a number of reasons, Ashwagandha supplementation lacks sufficient information to be considered effective for all proposed conditions [ 4 ]. However, several recent systematic reviews and meta-analyses have shown its potential and safety for controlling anxiety [ 12 ], fighting male infertility [ 13 ], improving the function of the reproductive system [ 14 ], serving as an adjuvant to the treatment of diabetes [ 15 ] and avoiding the deterioration of cognitive function [ 16 ]. However, it seems that some of the secondary metabolites of Ashwagandha could have some potential at the level of physical performance improvement, being responsible for various effects at the metabolic and physiological level through the regulation of certain anti-inflammatory and anti-oxidative pathways [ 4 , 17 ].…”
Section: Introductionmentioning
confidence: 99%